Growth and reproduction of the squid Illex coindetii Verany, 1839 in the central Mediterranean Sea - CERIOLA, L.; MILONE, N. (Mediterranean Marine Science, 2017)
Life span, growth and cost of reproduction of Illex coindetii were examined for the first time in the southern Adriatic Sea, central Mediterranean Sea. Age and growth were investigated through statoliths reading. Cost of reproduction was explored by studying the relative investment between somatic and gonad growth. The life span of I. coindetii was less than nine months in both sexes. Females (128-234 days) showed longer life span than males (124-178 days). In both sexes the linear model best described the mantle length-at age data, while the exponential model provided the best fit to the total weight-at-age data. In terms of mantle length, females grew faster than males (average growth rate was 1.33 mm day- 1 in females and 1.00 mm day-1 in males). In terms of total weight, no significant differences were highlighted between growth curves of males and females. Mantle length, total weight, mantle weight and fin weight increased up to the latest maturity stage in both sexes. Immature and maturing individuals showed poorer body condition than mature counterparts in both sexes. Some evidences of a reproductive strategy more similar to a multiple-spawning than to a single-spawning species were found.